First record of family Dipsocoridae (Hemiptera: Heteroptera: Dipsocoromorpha) from the Korean Peninsula and a new generic combination for Cryptostemma japonicum Miyamoto - Kim, Junggon; Kim, Wongun; Park, Jihwan; Jung, Sunghoon (Zootaxa, 2019)
The family Dipsocoridae is first reported from the Korean Peninsula based on a finding of Pachycoleus japonicum (Miyamoto, 1964) comb. nov. Detailed description of male and female genitalia of P. japonicum is provided. A new generic combination for P. japonicum is proposed. The ambiguous characters for generic concept in previous work and implications to assign genus for the species in other faunas are discussed. Biological note on the unique habitat of the species unlike congeners is presented with illustrations and photographs. A key to the Korean dipsocoromophan families (species) is also provided.